Machine Maintenance Management System - Heng, Cheng Bu (2001)

(untitled)
This projects develops a machine maintenance system to be used in high technology manufacturing industries, machine performance influences the entire manufacturing operation, from product quality to on-time delivery. Thus, machine maintenance management system is essential to improve machine performance while reducing production costs immensely. Rational Unifield Modeling Processs is used develop the analysis and design models of the machine maintenance management system. An integration of Web-based application (PWS) and Microsoft Visual Basic 6.0 is used to develop the system interface. Microsoft Access is used to develop the system database. Upon the system prototyping process, the system has been tested in MKPI (Matsushita Kotobuki Peripheral Indonesia). Further work, such as modification of machine, software and setup of networking between computer production line and office could be done to materialize the full implementation of the system functionality.